Mulangos e mulangas registram a possibilidade de uma reflexão teológica afroamericana - Centro Atabaque - Teologia e Cultura Negra - Silva, Marcos Rodrigues da (2014)
The central objective of this study was to investigate and pursue a reflection from the african historical movements already made by other traditions of belief and knowledge; analysis in this course the writings and reflections of Atabaque Center - Black Culture and Theology with the statements of Anibal Quijano new variables come across the idea of a hierarchical relationship between the colonizer and the colonized; and Memmi that states - not all colonizing this inevitably destined to become a colonialist. Anyway, we tried to demonstrate that faced with the contributions of e saberes beliefs of black people in the African American diaspora, with universal knowledge and technological-scientific reflection.